Perfectionism and anxiety sensitivity as predictors of trait anxiety - Lauri Korajlija, Anita; Jokić-Begić, Nataša (2010)
The aim of this study was to examine the hierarchical relationship between the general vulnerability factors of trait anxiety and the specific vulnerability factors of anxiety sensitivity and perfectionism as hypothesized in the Integrative Hierarchical Model of Anxiety. The study was conducted on a normative nonclinical sample of adults (N=1475). Following measures were used: the State-trait Anxiety Inventory, the Positive and Negative Perfectionism Scale and Anxiety Sensitivity Index. The results showed that anxiety sensitivity and perfectionism were significant predictors of trait anxiety with significant gender differences. Dimensions of anxiety sensitivity and perfectionism together explained 54.3% of trait anxiety variance in female adults. Psychological concerns, negative perfectionism and interaction between physical concerns and positive perfectionism were risk factors, while positive perfectionism, interaction between positive and negative perfectionism and interaction between positive perfectionism and psychological concerns were protective factors. Dimensions of anxiety sensitivity and perfectionism together explained 46% of trait anxiety variance in adult men. Psychological concerns and negative perfectionism were risk factors and positive perfectionism was a protective factor. Study results confirmed a part of the Integrative Model of Anxiety and demonstrated that anxiety sensitivity and perfectionism were significant risk factors for trait anxiety. Question about different levels of risks they belong to was raised for future research. Significant interactions between dimensions of anxiety sensitivity and positive perfectionism indicate the complex nature of adaptive perfectionism, which has significant theoretical and practical implications.
Projekt MZOS
ENG